Citizens' attitudes towards tax evasion: demographic profile, perception of fairness and relative seriousness / Nur Quratun 'Aini Haron - Haron, Nur Quratun 'Aini (2015)
This is an exploratory study conducted in Malaysia whereby it focuses on the citizens' attitudes toward tax evasion and to determine whether demographic profile and perception of fairness affect the attitudes of the Malaysian citizens on tax evasion. In addition, this study examined whether citizens in Malaysia view tax evasion as an acceptable activity and examined the relative seriousness of tax evasion as compared to other offences. The sample size of this study is 173 comprising of salary earning and retirees located throughout the Southern and Central regions. This study found that only age and nature of employment have a significant difference on the attitudes towards tax evasion. Respondents' gender, level of income and level of education seemed to bear no significant difference to their attitudes towards tax evasion. Apart from that, perception of fairness is also found to have no significant relationship with the citizens' attitudes towards tax evasion. Surprisingly, this study found that citizens in Malaysia find it acceptable to evade on all sizes of income, be it "a small part", "a large part", or "all part" of their income. Tax evasion also was not considered as a serious offence as it has been ranked as the least severe as compared to suicide, abortion, homosexuality, prostitution, wife beating, divorce, accepting a bribe, avoiding fare on a public transport and claiming government benefits which you are not entitled to. This study may be useful and would be able to facilitate the tax authorities in evaluating and reviewing the current tax system. It is crucial so as to ensure that people will not take tax evasion lightly.